Clinical dyspnea scenario: Using high-fidelity situation simulation teaching program to evaluate learning effectiveness for clinical junior and pre-clinical nurses - Liu, Yu-Hsin; Subeq, Yi-Maun; Lin, Po-Han (Frontiers in Psychology, 2023)
Background Confronting a patient’s breathing difficulties, clinical junior nurses often do not know how to respond, and fail to give proper evaluation and treatment. Sudden changes in the condition make the clinical nursing novices feel pressured, and even, frustrated. Objectives This study aims at exploring the effectiveness of the high-realistic situational simulation of dyspnea teaching program for pre-clinical and clinical 1st year nurses after graduation. Design This study adopts a quasi-experimental repeated measure pre-post-test design study with nonequivalent control group pre- and post-test research design. A total of 135 subjects participated in the research: nurses, post graduate year (NPGY) (N = 69), have been employed in the adult ward of a medical center for less than 1 year; and pre-clinical nurses (N = 66), 3rd-year nursing students with nurse licenses from a university in the central part of Taiwan. Simulation-based education instructed and incorporated into the high-realistic situation simulation dyspnea teaching program. Questionnaires were used to measure the effectiveness of learning, data were analyzed with SPSS version 20.0, and the scores were repeatedly measured with the generalized estimating equation. Results For “cognition, skills, attitude, self-efficacy, teamwork,” NPGY and pre-clinical nurses’ post-tests are better than pre-tests, with statistically significant results. NPGY nurses’ “skills,” “attitude” and “teamwork” learning effectiveness are better than those of the pre-clinical nurses. Conclusion The high-realistic situational simulation of dyspnea teaching program can significantly improve the learning effectiveness of NPGY nurses and pre-clinical nurses in the clinical evaluation and treatment of dyspnea.